The dinner [videorecording (DVD)] - Moverman, Oren; Gere, Richard, 1949-; Linney, Laura; Coogan, Steve; Hall, Rebecca, 1982-; Koch, Herman, 1953- (Lionsgate, 2017)
It is a dark psychological thriller about a fierce showdown between two couples during the course of an ornately prepared meal at a fancy restaurant. When Stan Lohman, a popular congressman running for governor, invites his troubled younger brother Paul and his wife Claire to join him and his wife Katelyn for dinner at one of the town's most fashionable restaurants, the stage is set for a tense night.